2013
DOI: 10.1177/0956797613498395
|View full text |Cite
|
Sign up to set email alerts
|

Turning Body and Self Inside Out

Abstract: Prominent theories highlight the importance of bodily perception for self-consciousness, but it is currently not known whether bodily perception is based on interoceptive or exteroceptive signals or on integrated signals from these anatomically distinct systems. In the research reported here, we combined both types of signals by surreptitiously providing participants with visual exteroceptive information about their heartbeat: A real-time video image of a periodically illuminated silhouette outlined participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(130 citation statements)
references
References 44 publications
(83 reference statements)
10
118
1
Order By: Relevance
“…They found that a virtual arm with a realistic appearance co-located with the subject's actual arm is sufficient to induce the illusion of ownership of the virtual arm. In addition to visual and tactile signals, recent work suggests that manipulations of interoceptive signals, such as heartbeat, can also influence our experience of embodiment (Aspell et al, 2013;Seth, 2013).…”
Section: Direct Ui-manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that a virtual arm with a realistic appearance co-located with the subject's actual arm is sufficient to induce the illusion of ownership of the virtual arm. In addition to visual and tactile signals, recent work suggests that manipulations of interoceptive signals, such as heartbeat, can also influence our experience of embodiment (Aspell et al, 2013;Seth, 2013).…”
Section: Direct Ui-manipulationmentioning
confidence: 99%
“…Rather than unsatisfactory reproductions of familiar modes of interaction, the technology should be developed with an eye toward "expanding and reinventing our sense of body and action" (2003, p. 111). Consider, for example, using a combination of substitutional and augmented reality to see a representation of some of the physiological states of your partner who is many miles away -such as a soft flash over the body in synchrony with the heartbeat (as in Aspell et al, 2013). That and similar uses of the technology could plausibly enhance embodied (though mediated) social interaction.…”
Section: Neglect Of Others and The Physical Environmentmentioning
confidence: 99%
“…As detailed below, those findings actually neither refute nor confirm the subjective frame hypothesis, because they tap onto a different issue. With a few exceptions [80], the above-listed studies were inspired by the baroreceptor hypothesis developed by Lacey & Lacey [59,60]. Briefly, baroreceptors located in arterial walls register changes in blood pressure at each heart cycle as well as changes in mean blood pressure, and trigger the socalled baroreflex to maintain a stable blood pressure.…”
Section: (D) What Those Studies Do and Do Not Tell Us About Subjectivmentioning
confidence: 99%
“…However, the relationship between interoception and body representation has been investigated also in the context of the virtual body illusion (Aspell et al, 2013) and virtual RHI (Suzuki, Garfinkel, Critchley & Seth, 2013). In both studies, visual feedback of participants' own heartbeat was provided 'on-line' (i.e.…”
Section: Introductionmentioning
confidence: 99%